Social Cohesion at the Centre - Cenic, Svetlana; Hackaj, Ardian; Kapetanovic, Amer; Koppa, Maria Eleni; Qorraj, Gazmend; Spasojevic, Dusan; Tevdovski, Dragan; Uljarevic, Daliborka (Friedrich Ebert Stiftung, 2015)
Prosperity and stability in the Western Balkans can be achieved only by a joint focus on economic and social questions within the framework of a new policy approach based on social cohesion. When revisiting its enlargement policy, the European Commission should set out intermediate steps to keep the process alive. A new social and economic model needs to be implemented in the Western Balkans. The social model should promote progressive taxation and social protection programmes designed to reduce income and wealth inequalities. A new economic model focused on an added value economy should replace the current neoliberal model. Fiscal transparency and open governance are the first steps towards building institutions that enable citizen participation in decision-making and create a level playing- field more conducive to economic prosperity in the Western Balkans. Fighting for meritocracy and eliminating political patronage is possible only by strengthening the mechanisms of democratic control.